The direct electrophilic cyanation of β-keto esters and amides with cyano benziodoxole. Issue 2 (19th November 2014) - Wang, Yao-Feng; Qiu, Jiashen; Kong, Dejie; Gao, Yongtao; Lu, Feipeng; Karmaker, Pran Gopal; Chen, Fu-Xue
Abstract : Electrophilic cyanating agentC1 accomplishes the direct cyanation of β-keto esters and amides without any catalyst and base. Abstract : The direct electrophilic α-cyanation of β-keto esters and amides has been developed using a hypervalent iodine benziodoxole-derived cyano reagent. The procedure is accomplished within 10 min and without the use of any catalyst in DMF, at room temperature. Thus, the highly functionalized quaternary carbon-centered nitriles were produced in high to excellent yields.